2000
DOI: 10.1161/01.res.86.6.700
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Dysfunction Caused by Myocardium-Specific Expression of a Mutant Thyroid Hormone Receptor

Abstract: Abstract-Thyroid hormone deficiency has profound effects on the cardiovascular system, resulting in decreased cardiac contractility, adrenergic responsiveness, and vascular volume and increased peripheral vascular resistance. To determine the importance of direct cardiac effects in the genesis of hypothyroid cardiac dysfunction, the cardiac myocyte was specifically targeted with a mutant thyroid hormone receptor (TR)-␤ (⌬337T-TR-␤ 1 ) driven by the ␣-myosin heavy chain (␣-MHC) gene promoter. As a control in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
7
30
1
Order By: Relevance
“…These data also confirmed that the adult mutant mice devoid of TR␣ are bradycardic (14,15,(22)(23)(24). They further show that the basal HR of both WT and mutant pregnant mice is slightly elevated as compared with nonpregnant animals with the respective genotype.…”
Section: Discussionsupporting
confidence: 77%
“…These data also confirmed that the adult mutant mice devoid of TR␣ are bradycardic (14,15,(22)(23)(24). They further show that the basal HR of both WT and mutant pregnant mice is slightly elevated as compared with nonpregnant animals with the respective genotype.…”
Section: Discussionsupporting
confidence: 77%
“…1A). The artificially reduced levels of elastance and contractile function, and enhanced diastolic stiffness measured with these smaller balloons are consistent with values measured previously (Brooks & Apstein, 1996;Kameyama et al 1998;Pazos-Moura et al 2000;Sam et al 2000). Thus, low contractility in some prior studies may reflect the effects of inadequate balloon design.…”
Section: Normoxic Function and Stabilitysupporting
confidence: 87%
“…Estimates of left ventricular developed pressure and +dP/dt for isolated mouse hearts vary from as low as 5MO mmHg and 1000-3000 nlmHg s-', respectively Kameyama et al 1998;Sat0 et al 1998;Gyurko et al 2000;Pazos-Moura et al 2000;Zhao et al 2000;MacGowan et al 2001), to greater than 110 mmHg and 4000-6000 mmHg s-', respectively (Brooks & Apstein, 1996;Headrick et al 2000a;Sam et al 2000). These values compare with in situ left ventricular pressures of -1 10 mmHg (Georgakopoulos et al 1998), and +dPldt values L 8000 mmHg s-' (Hoit et al 1997;Georgakopoulos et al 1998).…”
Section: Normoxic Function and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we used mice that express the TRbD337T, which cannot bind TH, being constitutively associated with CoR and acting as a potent dominant negative inhibitor of the WT TR (Safer et al 1998, Pazos-Moura et al 2000, Hashimoto et al 2001). This mouse model reproduces the human syndrome of resistance to TH (Hashimoto et al 2001).…”
Section: Introductionmentioning
confidence: 99%